Case report: Total percutaneous post-closure of femoral arterial access sites after veno-arterial extracorporeal membrane oxygenation - Tian, Lun; Zhang, Libin; Zhang, Naiding; Xu, Xin; Xu, Yongshan; Liu, Zhenjie; Huang, Man (Frontiers in Medicine, 2022)
VA-ECMO stands for veno-arterial extracorporeal membrane oxygenation, which is a form of circulatory and gas exchange support. Following VA-ECMO, total percutaneous closure of the site of femoral arterial puncture with perclose Proglide (PP) has become widespread, enhancing patient comfort and lessening the incidence of wound infections and lymphatic fistulas in a short closure time. The preclose technique with perclose Proglide provides numerous benefits, however, it prolongs extra time during¬ the VA-ECMO procedure, adds additional post-operative care to workloads, and increases the potential for Proglide stitch infection. The modified techniquepercutaneous post-closure, described here by a case of a 65-year-old man with heart attack who underwent VA-ECMO, is a simple, rapidly applied technique to wean VA-ECMO also suitable for emergency cannulation. The patient was administered mechanically ventilated and sedated and the femoral artery access site and evaluated by ultrasound for precise positioning, then the VA-ECMO arterial cannula was withdrawn, and a 0.035-in guidewire was left in the artery. The first set of sutures was deployed after the Proglide device was inserted over the guidewire. The second sutures were then replaced in the same way but at a different angle. After hemostasis was achieved, the guidewire was removed, and additional manual compression was used to control any residual blood seeping. No hematoma, pseudoaneurysm, major bleeding, minor bleeding, acute arterial thrombosis, arteriovenous fistula, groin infection, lymphocele, or arterial dissection and stenosis occurred during the periprocedural period or during the 30-day post-procedural follow-up. In conclusion, the standardized algorithm we established, total percutaneous post-closure of femoral arteriotomies utilizing Perclose ProGlide device is feasible and safe with a low incidence of access site complications.